777 Changing Student Perceptions of Surgical Careers. (12th October 2021) - Karunaratne, D; Peat, F; Rozewicz, S; Tupper, L; Perera, E; Samuel, T; Buksh, M
Abstract: Aim: Increasing student interest in pursuing a surgical career at an undergraduate level. Background: Data suggests that interest in surgical specialties may be declining, even from as early on as medical school. However, studies suggest that engagement with extra-curricular activities influences their likelihood to pursue surgical careers. Our study aimed to assess changes in student perception towards surgical careers following participation in a three-week surgical course. Method: Students on placement at St Peter's Hospital, Chertsey were invited to a course of 3 one-hour sessions covering practical surgical skills and lectures. Participants were tutored by Foundation-Year-Two doctors, with oversight of a surgical clinical teaching fellow and senior consultant. Students completed pre- and post-course surveys focusing on surgical interest, surgical skill confidence, placement-participation, and career preparation. The course was delivered through two cycles. Results: Cycle one showed statistically significant improvements in suturing-confidence (mean increase 4.05 out of 10, p = 0.001), confidence in hand-ties (3.63 out of 10, p = 0.015) and understanding of developing a surgical portfolio (mean increase 1.95 out of 10, p = 0.005). After a second cycle, including the introduction of a surgical portfolio development lecture, students demonstrated a statistically significant improvement in mean scores across all areas. Notably, interest in pursuing a surgical career increased from mean 5.85/10 to 8.8/10 (p = 0.028). Conclusions: We demonstrate that a short and easily accessible course can significantly improve student interest and understanding of a surgical career; equipping them with fundamental skills to pursue engagement at the undergraduate level.